Biochemistry of maternal and umbilical cord blood in Cerro de Pasco (4,200 m.) - Guerra García, Roger (2015)
The authors have studied several blochemical parameters in maternal and cord blood from 18 normal deliveries ocurred in Cerro de Pasco, at an altitude of 14000 ft.; as control 16 cases attended at the Maternity Hospital in Lima (445 ft.9 were studied. Newborn weights were similar: 3205 ± 343 g in C. P. and 3086 ± 495 g in Lima; Apgar score was also similar 8.4 and 8.2  respectively. In cord blood mean values in C. P. were: Hematocril 52.5 % ± 6.5 %; pottassium 6.0 ± 0.9, sodium 146 ± 9.3, chloride 110 ± 7.7 m.Eq ./L creatinine 1.14 ± 0 .3, glycemia 67 ± 19 and urea 32.2 ± 12.9 mg.%. Same determinations in Lima were: Hematocrit 48.8 % ± 4.5, similar to  C. P. (p > 0.05]; pottassium 5.0 ± 0.4, sodium 136 ± 2.2 and chloride 103 ± 2.6 m.Eq ./L; the electrolite valves were lower in Lima with p values of > 0.006, < 0.02 and < 0.001 respectively. Creatinine was 0.84 ± 0.3 mg.% lower than C. P. (p < 0.02); glycemia was 72 ± 13 and urea 33.8 ± 4.7 both values similar to those registered in C. P. (p > 0.4 and > 0 .5). In maternal blood mean values were as follows: In C. P. hematocrit 45 % ± 3; pottassium 4.6 % ± 1.1, sodium 138 ± 7.1, chloride 103 ± 5.7 m.Eq./L; creatinine 1.04 ± 0.1, glycemia 76.4 ± 13.9 and urea 30.0 ± 13.2 mg.%. Some determinations in Lima were: Hematocril 38% ± 4.6 significantly lower than C. P. (p 0.001) pottasium 4.5 ± 0.7, sodium 136 ± 12.9 and chloride 102 ± 5.3, values similar to C. P. Creatinine was 0.81 ± 0.2 lower than C. P. (p < 0.02) but glycemia and urea had higher concentration: 87 ± 6.2 and 43.5 ± 5 mg. with p values < 0.05 and 0.002 respectively. It is concluded that newborns at high altitude present several biochemical characteristics that could be related to the doubled neonatal mortality observed in the Andean region.